2019
DOI: 10.1111/ppe.12608
|View full text |Cite
|
Sign up to set email alerts
|

Variability in birthweight, birthweight charts, and adverse outcomes: Is the “right size” the right question?

Abstract: In this issue of Paediatric and Perinatal Epidemiology, Choi and colleagues 1 present novel nationwide Australian data on adverse perinatal outcomes of immigrants. One objective was to evaluate whether infant mortality, morbidity, and size at birth varied by maternal country of birth. There is a substantial body of literature indicating that newborn outcomes do vary by maternal birthplace, as documented by the systematic reviews and meta-analyses cited by the authors. Therefore, their findings of maternal birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Additionally, many of these cohorts are not necessarily representative of the general population as only women who agree to participate are included. Population‐based inter‐ and transgenerational cohorts have been established within administrative and perinatal databases in several places, including the Scandinavian countries and Canada, but some of these studies are limited with respect to the amount of antenatal and maternal behavioural data that is available. In comparison to experimental studies conducted in animals, associations observed in epidemiologic cohort studies may be attributable, separately or in combination, to epigenetic modifications influenced by in utero exposures, genetics, and environments or behaviours shared among family members.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many of these cohorts are not necessarily representative of the general population as only women who agree to participate are included. Population‐based inter‐ and transgenerational cohorts have been established within administrative and perinatal databases in several places, including the Scandinavian countries and Canada, but some of these studies are limited with respect to the amount of antenatal and maternal behavioural data that is available. In comparison to experimental studies conducted in animals, associations observed in epidemiologic cohort studies may be attributable, separately or in combination, to epigenetic modifications influenced by in utero exposures, genetics, and environments or behaviours shared among family members.…”
Section: Introductionmentioning
confidence: 99%